Model to study the non-linear radiation heat transfer in the stagnation-point flow of power-law fluid. Issue 5 (1st June 2015) - Mustafa, M.; Mushtaq, Ammar; Hayat, T.; Alsaedi, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate non-linear radiation heat transfer problem for stagnation-point flow of non-Newtonian fluid obeying the power-law model. Power-law fluids of both shear-thinning and shear-thickening nature have been considered. Design/methodology/approach – Boundary layer equations are non-dimensionalized and then solved for the numerical solutions by fourth-fifth order Runge-Kutta integration based shooting technique. Findings – The results reveal an existence of point of inflection for the temperature distribution for sufficiently large wall to ambient temperature ratio. Moreover temperature increases and heat transfer from the plate decreases with an increase in the radiation parameter. Heat transfer rate at the sheet is bigger in dilatant (shear-thickening) fluids when compared with the pseudoplastic (shear-thinning) fluids. Originality/value – Different from the linear radiation heat transfer problem (which can be simply reduced to rescaling of Prandtl number by a factor containing the radiation parameter), here the energy equation is strongly non-linear and it involves an additional temperature ratio parameter w=Tw/T∞. This parameter allows studying the thermal characteristics for small/large temperature differences in the flow.